The impact of endotoxin on jejunal tissue oxygenation. (August 2017) - Pajk, Werner; Stadlbauer, Karl‐Heinz; Kleinsasser, Axel; Kotzinger, Oskar; Ulmer, Hanno; Hasibeder, Walter; Knotzer, Hans
Abstract: Objective: We examined the effects of systemic ETX on jejunal mucoal microcirculatory parameters in anesthetized pigs. Methods: Jejunal mucosal tissue PO2 was measured employing Clark‐type surface oxygen electrodes. Oxygen saturation of jejunal microvascular hemoglobin was determined by tissue reflectance spectrophotometry. Jejunal microcirculatory blood flow was assessed by laser Doppler flowmetry. Microvascular conductance and rhythmical oscillation of the tissue PO2 were calculated. Systemic hemodynamic variables, mesenteric venous and systemic acid base and blood gas variables, and lactate measurements were recorded. Measurements were taken at BL and after Escherichia coli LPS administration in 20 minutes intervals for 110 minutes. Results: ETX infusion led to a significant ( P <.05) decrease of PO2 muc (from 24±4 to 8±4 mm Hg) and microvascular HbO2 (from 41±13 to 24±12%). Microcirculatory conductivity increased in ETX animals, microvascular blood flow remained unchanged (PU; from 228±45 to 232±58). ETX induced an increase in oscillation frequency of mucosal tissue oxygenation. Conclusions: Endotoxinemia resulted in a significant depression of mucosal tissue oxygenation despite a constant microcirculatory blood flow. This impairment of tissue oxygenation resulted in an increase in the vasomotion pattern in a futile attempt to counteract the undersupply of oxygen to the jejunal tissue.